The voyages of doctor dolittle ebook - Lofting, Hugh (Doctor Dolittle, 2012)
Doctor Dolittle takes on an apprentice, Tommy Stubbins, as they set out to find Long Arrow, the world's greatest naturalist. Their quest takes them to the Mediterranean, to South America, deep under the sea, and even to a floating island. This second Dolittle book by Hugh Lofting won the Newbery Medal in 1923.